RESEARCH OF METHODS FOR IMPROVING THE PHYSICAL FITNESS OF LAW ENFORCEMENT OFFICERS (Scientific journal of the Fergana State University, 2026)
In this article, the physical readiness of law-enforcement personnel and emergency management workers (rescuers) is comprehensively examined and analyzed based on applied standards and scientific evidence. For the MPOETC/Cooper tests widely used in foreign police agencies (1-minute sit-ups, 1-minute push-ups, and runs over 300 meters and 1.5 miles), minimum benchmarks for the 20–49-year age range were compiled [1]–[3]. The findings indicate five-year decline trends during service in several measures (vertical jump, push-ups, VO₂max), as documented in prior studies [4]. For rescuers, the eight CPAT events (overall time limit 10:20) and the 12 MET (≈42 ml·kg⁻¹·min⁻¹) minimum requirement specified by NFPA 1582 are presented systematically [9]–[12]. Based on these results, a practical program is proposed that combines age-appropriate periodization (HIIT + strength), injury prevention, and wellness components (sleep, nutrition, stress). This approach reduces the gap between entry standards and actual professional task performance and enhances on-duty safety.